Surgically treated symptomatic calcified chronic subdural hematoma - Achmad Adam; Syaiful Anwar; Muhammad Azhary Lazuardy; Bilzardy Ferry Zulkifli (Indoscholar, 2020)
Calcified chronic subdural hematoma (SDH) or armoured brain is especially rare with only slight pathophysiology understanding. It happened after head trauma, subdural effusion, meningitis, or as a sequel of VP Shunt. But there is no definite mechanism of neither the pathogenesis nor the management. Because these patients have a thick calcified inner membrane, the optimal surgical procedure for armoured brain’s patient has not been established. Moreover, it is also difficult to obtain good re-expansion of the brain after surgery. A calcified chronic subdural hematoma is less likely happened in adults or elder rather than children or young adults. Management of calcified chronic subdural hematoma is mostly individualized. With seizures, careful monitoring of the anticonvulsant therapy is required. The indications of surgical procedure can be features of raised intracranial pressure, headache, or neurological deterioration. The surgical strategies depend on calcification’s thickness and extension. This study was a preliminary study of Achmad Adam’s research project. This was a descriptive observational research with a case report design. We report a rare case of calcified chronic subdural hematoma in the elderly, presenting with progressive neurological deficit and acute raised intracranial pressure, which was managed surgically to facilitate cerebral re-expansion and inhibit probable brain atrophy. Therefore, authors intended to share a case report regarding a rare chronic subdural hematoma and its management, so hopefully it could be acknowledged by other surgeons as something to learn from.